Do platelet apoptosis, activation, aggregation, lipid peroxidation and platelet-leukocyte aggregate formation occur simultaneously in hyperlipidemia? - ŞENER, AZİZE; ÖZSAVCI, DERYA (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
Objectives: The circulating lipoproteins may cause some abnormalities in platelet composition and function in hypercholesterolemia. The aim Of this Study was to investigate whether platelet apoptosis, platelet activation, platelet aggregation, platelet-leukocyte aggregate (PLA) formation and lipid peroxidation occur simultaneously in hyperlipidemia. Design and methods: Expression of GpIIb/IIIa (CD41a), P-selectin (CD62-P), platelet-bound fibrinogen (antifibrinogen), platelet membrane phosphatidylserine (PS), platelet-monocyte aggregates (mono-PLA) and platelet-neutrophil aggregates (neut-PLA) was measured in eight hyperlipidemic and eight normal subjects using flow cytometry. ADP (10 mu M) was used to activate platelets. Furthermore, ADP induced platelet aggregation responses, platelet malondialdehyde (MDA) and glutathione (GSH) levels were determined. Results: Before platelet activation, platelet CD62-P, anti Fibrinogen, annexin-V, mono-PLA, neut-PLA and platelet MDA levels as well as platelet aggregation responses in the hyperlipidemics were significantly higher than those in the controls (P < 0.01, P < 0.01, P < 0.01, P < 0.001, P < 0.001, P < 0.01, P < 0.001, respectively), whereas GpIIb/IIIa expression and GSH levels were not different significantly (P > 0.05). In the control group, CD62-P, antifibrinogen and annexin-V levels increased significantly after ADP activation (P < 0.05, P < 0.05, P < 0.01, respectively). In hyperlipidemic Subjects, annexin-V expression increased significantly after activation (P < 0.01), whereas expression of GpIIb/ IIIa, CD62-P and anti fibrinogen remained unchanged (P > 0.05). The levels of total cholesterol (T-CHO), low density lipoprotein cholesterol (LDL-C), serum fibrinogen (S-FGN) and high density lipoprotein cholesterol (HDL-C) in patients were found to be correlated with platelet CD62-P, anti Fibrinogen, annexin-V, mono-PLA and MDA. Conclusions: In conclusion, it seems that in hyperlipidemia, some platelets are in an activated state in circulation, and that increased lipid peroxidation, early apoptosis, platelet-leukocytes aggregate formation and platelet aggregation altogether accompany this process. (C) 2005 The Canadian Society of Clinical Chemists. All rights reserved.
Keywords: hyperlipidemia; apoptosis; annexin-V; platelet activation; platelet-leukocyte aggregates; platelet MDA; GSH; GpIIb/IIIa; P-selectin; FLOW-CYTOMETRY; FIBRINOGEN BINDING; WHOLE-BLOOD; P-SELECTIN; EXPRESSION; MICROPARTICLES; LIPOPROTEINS; SECRETION; VIVO